SHORT TERM RESULTS OF PRIMARY ACRYSOF HYDROPHOBIC ACRYLIC FOLDABLE INTRAOCULAR LENS IMPLANTATION IN CHILDREN AT PRIMARY CHILDREN MEDICAL CENTER UNIVERSITY OF UTAH USA: Hydrophobic Acrylic Foldable Intraocular Lens Implantation - Sethi, Sadia; Hussain, Ibrar; Sethi, Muhammad Junaid (Pakistan Armed Forces Medical Journal, 2009)
Objectives: To study short term results of primary acrysof hydrophobic acrylic foldable intraocular lens implantation in children. Study design: A descriptive hospital based study Place and duration of Study: Pediatric Eye Unit, Primary Children Medical Center, University of Utah USA, where study was conducted from 1st July 2004 to 31st December 2007. Patients and Methods: Thirty five children aged 2 years to 13 years with congenital cataract who underwent phaco aspiration with posterior capsulotomy and anterior vitrectomy with acrysof hydrophobic acrylic foldable intraocular lens implantation in year 2004 to 2007 were included in the study. Outcome measures were visual acuity, clarity of the visual axis, postoperative inflammation and intra ocular pressure measurement. Results: Out of 35 children 4 had bilateral cataract and 31 had unilateral cataract. There was family history of congenital cataracts in 3 children. Preoperatively 25 eyes (64.1%) had visual acuity of < 20/80, 12 eyes (30.8%) had 20/80 and 2 eyes (5.1%) had 20/60. Two weeks postoperatively 28 eyes (71.7%) had visual acuity of 20/20, 8 eyes (20.7%) of 20/40 and 3 eyes (7.6%) 20/60. One year after surgery 9 eyes (23.07%) had visual acuity of 20/20, 12 eyes (30.76%) 20/40, 6 eyes (15.39%) 20/60, 3 eyes (7.70%) 20/80 and 9 eyes (23.08%) had visual acuity of < 20/80. Two weeks postoperatively 31 eyes (79.50%) were emmetrope and 8 eyes (20.50%) had astigmatism. One year after surgery 33 eyes (84.6%) were myope and 6 eyes (15.4%) had astigmatism. At the end of first year postoperatively children age 2-5 years showed mean change of refraction of 2.5 diopters, 6-9 years showed 2 diopters and 10-13 years showed 1 diopter change after one year. Postoperative inflammatory membranes occurred in 9 eyes (23.07%). Five eyes (12.8%) responded to topical steroids while 4 eyes (10.2%) required pars plana membranectomy. Visual axis/posterior capsular opacification occurred in 10 eyes (25.64%). Secondary posterior capsulotomy was performed in 9 eyes (23.07%) while Neodynium Yag Laser capsulotomy was performed in one eye (2.56%). Intraocular pressure recorded during postoperative period was normal in all the ages. Conclusions: The primary acrysof hydrophobic acrylic foldable intraocular lens implantation in children with posterior capsulotomy and anterior vitrectomy is a safe technique resulting in good visual acuity and normal intraocular pressure measurement postoperatively. Visual axis/posterior capsular opacification, postoperative inflammatory membranes and myopic shift are recognized complications of hydrophobic acrylic intraocular lens implantation.